Sintesis Dan Karakterisasi Membran Silika Dengan Variasi Aditif Polyethylene Glycol (Peg) Untuk Pengolahan Limbah Cair Hotel - Nandra Saputra; Jhon Armedi Pinem; Syamsu Herman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pollution that come from hotel liquid waste could reduce water quality on surrounding area. One of the ways to overcome the water pollution that come from hotel liquid waste are using membrane technology. In this study, silica membranes were made with 1;2;3 % (w/w) composition variation of Polyethylene Glycol (PEG) and hotel liquid waste treatment using silica membranes were carried out with 1;2;3 bar operating pressure variation. Silica membranes that have been made were characterized by flux measurement and rejection measurement. The highest value of flux was obtained on membranes with 3 % (w/w) PEG composition and 3 bar operating pressure, that is 22,246 L/(m2.hour). The lowest value of flux was obtained on membrane with 1 % (w/w) PEG composition and 1 bar operating pressure, that is 12,843 L/(m2.hour). The highest rejection values of BOD5, COD and TSS parameters were obtained from membranes with 1 (% w/w) PEG composition and 1 bar operating pressure, that are 69,14%, 77,88% and 86,76% respectively. The lowest rejection values of BOD5, COD and TSS parameters were obtained from membranes with 3 (% w/w) PEG composition and 3 bar operating pressure, that are 41,41%, 54,09% and 61,67% respectively.Keywords : membrane, polyethylene glycol (PEG), silica